(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Woman’s participation in India’s freedom struggle started as right on time as in 1817. Bhima Bai Holkar battled boldly against the British colonel ’Malcolm’ and crushed him in Guerilla fighting. Many women including Rani Channamma of Kittur, Rani Begam Hazrat Mahal of Avadh battled against British East India Company in the nineteenth century 30 years before the Primary War of Independence 1857. The pretended by women in the war of independence of 1857 was noteworthy and welcomed the reverence even leaders of the Revolt. Rani of Ramgarh, Rani Jindan Kaur, Rani Tace Bai, Baiza Bai, Chauban Rani, and Tapasvini Maharani daringly drove their troops into the war zone. Rani Lakshmi Bai Jhansi whose gallantry and magnificent leadership laid an extraordinary case of genuine patriotism. Indian women who joined the national movement had a place with taught and liberal families, and in addition those from the country zones and from all stroll of life, all ranks, religions and networks. Sarojini Naidu, Kasturba Gandi, Vijayalakshmi Pundit and Annie Besant in the twentieth century are the named which are recalled even today for their solitary contribution both in combat zone and in political field.